Jornalismo digital no sertão paraibano: mudanças e desafios do portal Diário do Sertão - Batista, Mikaely de Sousa (2023)
Technological advancement has brought significant changes to the field of journalism. The demand for news in various formats and the need for news organizations to cater to the audience's preferences have resulted in transformations in journalistic processes. The objective of this study was to analyze the processes of digital journalism and multimodality within the news portal Diário do Sertão, as well as the respective structural changes. More specifically, we aimed to identify how the process of content production and insertion occurs across different platforms. Our theoretical research was based on the concepts of convergence (ARANHA, 2014), transmedia storytelling (JENKINS, 2009), web journalism (CANAVILHAS, 2014), transformations in journalism (SILVA, 2016), multimodality (SALAVERRÍA, 2014), and journalism in the interior (ASSIS, 2013). Diário do Sertão has evolved in local journalism through multimodality, offering diverse content and utilizing different media formats to reach the audience. This approach contributes to raising the quality of the medium and differentiating it from competing outlets in the interior. The research helps to understand the growth of journalism in the interior, as it goes beyond metropolitan areas and the capital city.